Giant Tree Frog diversification in West and Central Africa: Isolation by physical barriers, climate, and reproductive traits. Issue 15 (28th September 2021) - Jaynes, Kyle E.; Myers, Edward A.; Gvoždík, Václav; Blackburn, David C.; Portik, Daniel M.; Greenbaum, Eli; Jongsma, Gregory F. M.; Rödel, Mark‐Oliver; Badjedjea, Gabriel; Bamba‐Kaya, Abraham; Baptista, Ninda L.; Akuboy, Jeannot B.; et al.
Abstract: Secondary sympatry amongst sister lineages is strongly associated with genetic and ecological divergence. This pattern suggests that for closely related species to coexist in secondary sympatry, they must accumulate differences in traits that mediate ecological and/or reproductive isolation. Here, we characterized inter‐ and intraspecific divergence in three giant tree frog species whose distributions stretch across West and Central Africa. Using genome‐wide single‐nucleotide polymorphism data, we demonstrated that species‐level divergence coincides temporally and geographically with a period of large‐scale forest fragmentation during the late Pliocene. Our environmental niche models further supported a dynamic history of climatic suitability and stability, and indicated that all three species occupy distinct environmental niches. We found modest morphological differentiation amongst the species with significant divergence in tympanum diameter and male advertisement call. In addition, we confirmed that two species occur in secondary sympatry in Central Africa but found no evidence of hybridization. These patterns support the hypothesis that cycles of genetic exchange and isolation across West and Central Africa have contributed to globally significant biodiversity. Furthermore, divergence in both ecology and reproductive traits appear to have played important roles in maintaining distinct lineages. At the intraspecific level, we found that climatic refugia, precipitation gradients, marine incursions, and potentially riverine barriers generated phylogeographic structure throughout the Pleistocene and into the Holocene. Further studies examining phenotypic divergence and secondary contact amongst these geographically structured populations may demonstrate how smaller scale and more recent biogeographic barriers contribute to regional diversification. Abstract : see also the Perspective by Bryan C. Carstens and Shelby P. Moshier Abstract : La sympatrie secondaire parmi les espèces sœurs est fortement associée à la divergence génétique et écologique. Ce modèle suggère que pour que des espèces étroitement liées coexistent en sympatrie secondaire, elles doivent accumuler des différences dans les traits qui contribuent à l'isolement écologique ou reproductif. Ici, nous avons caractérisé la divergence inter‐ et intra‐spécifique chez trois espèces de grenouilles arboricoles géantes dont les distributions s'étendent à travers l'Afrique de l'Ouest et Centrale. Avec des données génétiques, nous avons démontré que la divergence au niveau des espèces coïncide temporellement et géographiquement avec une période de fragmentation forestière à la fin du Pliocène. Nos modèles de niches environnementales ont soutenu une histoire dynamique de stabilité climatique, et ont indiqué que les trois espèces occupent des niches environnementales distinctes. Nous avons trouvé une différenciation morphologique modeste parmi les trois espèces mais une divergence significative dans le diamètre du tympan et les cris des mâles. De plus, nous avons confirmé que deux espèces sont présentes en sympatrie secondaire en Afrique Centrale mais n'avons trouvé aucune preuve d'hybridation. Ces résultats soutiennent l'hypothèse que les cycles d'échange génétique et d'isolement à travers l'Afrique de l'Ouest et Centrale ont contribué à une profonde concentration de biodiversité dans la région. De plus, la divergence des traits écologiques et reproducteurs semble avoir joué un rôle important dans le maintien de lignées distinctes. Au niveau intra‐spécifique, nous avons constaté que les refuges climatiques, les gradients de précipitation, les incursions marines et potentiellement les barrières fluviales ont généré une structure phylogéographique pendant le Pléistocène et jusqu'à l'Holocène. Des études examinant la divergence phénotypique et le contact secondaire entre ces populations géographiquement structurées pourraient démontrer comment des barrières biogéographiques à échelle plus petite et plus récentes contribuent à la diversification régionale.